1993
DOI: 10.1002/pen.760331904
|View full text |Cite
|
Sign up to set email alerts
|

Melt blending of ultra high molecular weight and high density polyethylene: The effect of mixing rate on thermal, mechanical, and morphological properties

Abstract: The blends of two different ultra high molecular weight polyethylenes (UHMWPE) and high density polyethylene (HDPE) were prepared in melt at different compositions and mixing rates in Brabender Torque Rheometer. The temperature build‐up due to the internal friction during melt blending was recorded and evaluated with respect to the change in the torque. The temperature at maximum torque was considered the fusion point temperature of the UHMWPE in the blend. This fusion point temperature was found to depend on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…Recently, Busby et al [16] obtained a novel nanostructured polymeric composite of polycarbonate (PC) and UHMWPE via a supercritical-fluid route. With regard to the blending of HDPE and UHMWPE, many research works have already been reported elsewhere [17][18][19][20][21]24,25]. For example, Tincer and Coskun [17] have prepared the blends of HDPE/UHMWPE at different compositions and mixing rates to study their mechanical properties, thermal oxidative degradation and morphologies.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Busby et al [16] obtained a novel nanostructured polymeric composite of polycarbonate (PC) and UHMWPE via a supercritical-fluid route. With regard to the blending of HDPE and UHMWPE, many research works have already been reported elsewhere [17][18][19][20][21]24,25]. For example, Tincer and Coskun [17] have prepared the blends of HDPE/UHMWPE at different compositions and mixing rates to study their mechanical properties, thermal oxidative degradation and morphologies.…”
Section: Introductionmentioning
confidence: 98%
“…With regard to the blending of HDPE and UHMWPE, many research works have already been reported elsewhere [17][18][19][20][21]24,25]. For example, Tincer and Coskun [17] have prepared the blends of HDPE/UHMWPE at different compositions and mixing rates to study their mechanical properties, thermal oxidative degradation and morphologies. Lim et al [20,21] have studied the suitability of HDPE/UHMWPE composites as biomaterials.…”
Section: Introductionmentioning
confidence: 98%
“…29 Therefore, low content of UHMWPE might be able to enhance PP even in the absence of compatibilizing agents under the conditions that the two components are mixed homogeneously. 30 The very high viscosity of UHMWPE in the molten state requires special processing methods. 30 In the case of PP/UHMWPE blend, the molten PP does not penetrate into the UHMWPE domains because of the poor miscibility of UHMWPE and PP.…”
Section: Effect Of Uhmwpe Addition On Wear Rate Of Pp and Its Blendsmentioning
confidence: 99%
“…18 However, the very high viscosity of UHMWPE in the molten state requires special processing methods. 15 Besides the used conventional compression molding, screw or ram-extrusion, coarse powder blending followed by compression molding, solvent blending, melt mixing, and sequential loading blending, 19 some novel effective techniques in polymer processing have been introduced. For instance, HDPE prepared by shear controlled orientation in injection molding (SCORIM) exhibited a fourfold increase in Young's modulus and a fivefold increase in ultimate tensile strength compared to that prepared by conventional injection molding, which was attributable to an oriented shish-kebab structure morphology developed during shear flow.…”
mentioning
confidence: 99%